Genotyping-by-Sequencing Reveals the Impact of Restocking on Wild Common Carp Populations of the Southern Caspian Basin - Jafari, Omid; Zeinalabedini, Mehrshad; Robledo, Diego; Fernandes, Jorge M. O.; Hedayati, Ali-Akbar; Arefnezhad, Babak (Frontiers in Ecology and Evolution, 2022)
Understanding the population structure and level of genetic diversity of wild populations is fundamental for appropriate stock management and species conservation. The common carp (Cyprinus carpio) is one of the most important bony fish throughout the southern coastline of the Caspian Sea, but captures of this species have seen a dramatic reduction during the last decade. As a consequence, a restocking programme has been put in place to maintain C. carpio populations, but its impact is not clear. In the present study, the population structure and genetic diversity of C. carpio in the Southern Caspian basin was determined using 17,828 SNP markers. A total of 117 individuals collected from four different locations in the southern Caspian basin and a farm were genotyped by genotyping-by-sequencing. The overall Fst obtained was 0.04, indicating a low level of differentiation between populations, and most genetic diversity was attributed to within population variation (97%). The low Fst values suggest that frequent migration events between different locations occur, and three migration events were inferred in the present study. However, each population still showed a distinct genetic profile, which allowed distinguishing the origin of the fish. This indicates that the ongoing restocking programme is maintaining the differences between populations to some extent. Nonetheless, high inbreeding and low heterozygosity were detected in all populations, suggesting that additional conservation efforts are required to protect C. carpio populations in the Southern coasts of the Caspian Sea.